The Public's Motivated Response to Supreme Court Decision-Making. (1st October 2016) - Badas, Alex
ABSTRACT: This article analyzes how the public perceives the Supreme Court's decision-making in Burwell v. Hobby Lobby Stores, Inc. (2014) and National Federation of Independent Business v. Sebelius (2012). Using theories of motivated reasoning and cognitive dissonance, I hypothesize that whether an individual approves or disapproves of the Court's decision will influence how they perceive the Court's decision-making. Specifically, those who approve of the Court's decision are more likely to be motivated to perceive the Court's decision-making in a legalistic fashion. However, those who disapprove of the decision are more likely to be motivated to perceive the Court's decision-making in a non-legalistic fashion. I find support for these hypotheses in analysis of both cases. The results presented in this article suggest that scholars need to consider how the public reacts to individual Court cases when studying how the public perceives the Court's decision-making. Further, these findings help explain the growing literature that finds individuals perceive the Court as less legitimate when the Court rules contrary to their interests.